Inhalation Dosage Forms: A Focus on Dry Powder Inhalers and Their Advancements - Sabrina Magramane; Kristina Vlahović; Péter Gordon; Nikolett Kállai-Szabó; Romána Zelkó; István Antal; Dóra Farkas (Pharmaceuticals, 2023)
In this review, an extensive analysis of dry powder inhalers (DPIs) is offered, focusing on their characteristics, formulation, stability, and manufacturing. The advantages of pulmonary delivery were investigated, as well as the significance of the particle size in drug deposition. The preparation of DPI formulations was also comprehensively explored, including physico-chemical characterization of powders, powder processing techniques, and formulation considerations. In addition to manufacturing procedures, testing methods were also discussed, providing insights into the development and evaluation of DPI formulations. This review also explores the design basics and critical attributes specific to DPIs, highlighting the significance of their optimization to achieve an effective inhalation therapy. Additionally, the morphology and stability of 3 DPI capsules (Spiriva, Braltus, and Onbrez) were investigated, offering valuable insights into the properties of these formulations. Altogether, these findings contribute to a deeper understanding of DPIs and their development, performance, and optimization of inhalation dosage forms.